Aunt Harriet's Underground Railroad in the sky - Ringgold, Faith (New York : Crown, 1995)
With Harriet Tubman as her guide, Cassie retraces the steps escaping slaves took on the Underground Railroad in order to reunite with her younger brother.
"Dragonfly books."
Includes bibliographical references.
Wilson's Children
School Library Journal
Child Study Children's Book Committee
4.7
Keywords: Tubman, Harriet, -- 1820?-1913 -- Fiction; Underground railroad -- Fiction; Brothers and sisters -- Fiction; African Americans -- Fiction; Tubman, Harriet, 1820?-1913 -- Fiction; Underground railroad -- Fiction; Siblings -- Fiction; African Americans -- Fiction